Mathematical Models of Mb/M/1 Bulk Arrival Queueing System - Ghimire, Sushil; Ghimire, R. P.; Thapa, Gyan Bahadur (Journal of the Institute of Engineering, 2014)
This paper deals with the study of bulk queueing model with the fixed batch size ‘b’ and customers arrive to the system with Poisson fashion with the rate λ and are severed exponentially with the rate μ. On formulating the mathematical model, we obtain the expressions for mean waiting time in the queue, mean time spent in the system, mean number of customers/work pieces in the queue and in the system by using generating function method. Some numerical illustrations are also obtained by using MATLAB-7 so as to show the applicability of the model under study. DOI: http://dx.doi.org/10.3126/jie.v10i1.10899 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 184–191